Transplant : from myth to reality - Tilney, Nicholas L. (Yale University Press, 2003)
"One of the most spectacular medical advances of the twentieth century, organ transplantation has become a generally effective and routine treatment for patients with organ failure. In this riveting book, a well-known expert in the fields of clinical transplantation and transplantation research traces the evolution of organ transplantation from its initial stirrings in the imaginations of the ancients to its current status as accepted treatment for nearly 40,000 patients each year. Drawing often on his own firsthand experience, Dr. Nicholas L. Tilney tells the story of the advances in organ transplantation, discusses how societal forces have driven its development, and reveals how its current success is marred by commercialism and exploitation of the less fortunate."--Jacket.